2008
DOI: 10.1111/j.1462-2920.2008.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Methanogen community in Zoige wetland of Tibetan plateau and phenotypic characterization of a dominant uncultured methanogen cluster ZC‐I

Abstract: Zoige wetland of Tibetan plateau is characterized by being located at a low latitude (33 degrees 56'N, 102 degrees 52'E) region and under the annual temperature around 1 degrees C. Previous studies indicated that Zoige wetland was one of the CH(4) emission centres in Qinghai-Tibetan plateau; in this study, the methanogen community in this low-latitude wetland was analysed based on the homology of 16S rRNA and mcrA genes retrieved from the soil. The results indicated that members of Methanosarcinales and Methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 47 publications
6
72
1
Order By: Relevance
“…Our results from the DGGE analysis are supported by cloning and sequencing of methyl coenzyme M reductase (mcrA) gene which also retrieved relatively rich diversity (25 different mcrA gene clones) of the methanogenic community in the Sitka stream hyporheic sediments. Similar richness in number of clones was also mentioned in a methanogenic community in Zoige wetland, where 21 different clones were found (Zhang et al 2008a), while 20 clones were described in the methane cycle of a meromictic lake in France (Biderre-Petit et al 2011). In addition, soils from Ljubljana marsh (Slovenia) showed 17 clones (Jerman et al 2009), for example.…”
Section: Methanogens Diversitysupporting
confidence: 66%
“…Our results from the DGGE analysis are supported by cloning and sequencing of methyl coenzyme M reductase (mcrA) gene which also retrieved relatively rich diversity (25 different mcrA gene clones) of the methanogenic community in the Sitka stream hyporheic sediments. Similar richness in number of clones was also mentioned in a methanogenic community in Zoige wetland, where 21 different clones were found (Zhang et al 2008a), while 20 clones were described in the methane cycle of a meromictic lake in France (Biderre-Petit et al 2011). In addition, soils from Ljubljana marsh (Slovenia) showed 17 clones (Jerman et al 2009), for example.…”
Section: Methanogens Diversitysupporting
confidence: 66%
“…Temperature is thought to be an important factor controlling methane production (Zeikus and Winfrey, 1976;Whiting and Chanton, 1993;Wik et al, 2014). However, it was reported that the majority of methanogens in Zoige wetlands was cold adapted and not sensitive to normal temperature changes (Zhang et al, 2008;Liu et al, 2011). Therefore, production rate of methane affected by temperature could have made a limited contribution to the variation of methane ebullition.…”
Section: Key Factors For the Extreme High Methane Ebullition From Lakmentioning
confidence: 99%
“…The temperature profile was identical to the study of Zhang et al (2008): initial denaturation at 94°C for 7 min followed by 30 cycles of denaturation at 94°C for 60 sec, annealing at 50°C for 45 sec and extension at 72°C for 90 sec, and a final elongation at 72°C for 7 min. PCR reaction mixture contains 5 μL Taq buffer, 3 μL dNTP (1.5 mmol/L, final concentration), 1 μL of each primer (0.4 mmol/L, final concentration), 0.2 μL BSA (10 mg/mL), 1 μL template DNA, 0.4 μL Taq DNA polymerase (5 U/ μL, Takara, Japan) and add RNase free dH 2 O (Takara, Japan) to a final volume of 50 μL.…”
Section: Pcr Amplificationmentioning
confidence: 99%